2012
DOI: 10.3390/md10010119
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Polysaccharide from the Brown Seaweed Sargassum graminifolium (Turn.), and Its Effects on Calcium Oxalate Crystallization

Abstract: Abstract:We investigated the effects of polysaccharides from the brown seaweed Sargassum graminifolium (Turn.) (SGP) on calcium oxalate crystallization, and determined its antioxidant activities. To examine the effects of SGP on calcium oxalate crystallization, we monitored nucleation and aggregation of calcium oxalate monohydrate crystals, using trisodium citrate as a positive control. We assessed antioxidant activities of SGP by determining its reducing power, its ability to scavenge superoxide radicals, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 42 publications
4
41
1
Order By: Relevance
“…Whereas, the efficacy was far lower than that of the reference ascorbic acid (99.54 ± 0.09%) at the concentration (1.0 mg/mL), the EC 50 of ascorbic acid was 0.18 mg/mL. The EC 50 of PCS were 0.11, 12.50 and 2.50 mg/mL for DPPH, hydroxyl and superoxide radical, which are similar to the EC 50 values of polysaccharides from Inonotus obliquus and Sargassum graminifolium (Mu et al, 2012;Zhang, Wu, Wang, & Lan, 2012). The results obtained from the test systems suggested that PCS have significant antioxidant activities, and the effects increase with increasing concentration of PCS, which are in accordance with the previous reports (Jiang, Wang, Liu, Gan, & Zeng, 2011).…”
Section: Scavenging Activity On Superoxide Radicalsupporting
confidence: 56%
“…Whereas, the efficacy was far lower than that of the reference ascorbic acid (99.54 ± 0.09%) at the concentration (1.0 mg/mL), the EC 50 of ascorbic acid was 0.18 mg/mL. The EC 50 of PCS were 0.11, 12.50 and 2.50 mg/mL for DPPH, hydroxyl and superoxide radical, which are similar to the EC 50 values of polysaccharides from Inonotus obliquus and Sargassum graminifolium (Mu et al, 2012;Zhang, Wu, Wang, & Lan, 2012). The results obtained from the test systems suggested that PCS have significant antioxidant activities, and the effects increase with increasing concentration of PCS, which are in accordance with the previous reports (Jiang, Wang, Liu, Gan, & Zeng, 2011).…”
Section: Scavenging Activity On Superoxide Radicalsupporting
confidence: 56%
“…that was also observed to inhibit calcium oxalate crystallization, a constituent of urinary kidney stones [23]; antioxidant activity in organic extracts from 30 species of Hawaiian marine algae, with the carotenoid fucoxanthin identified as the major bioactive antioxidant compound in the brown alga T. ornata [24]; screening of antioxidant activity in 18 cyanobacteria and 23 microalgae cell extracts identified Scenedesmus obliquus strain M2-1, which protected against DNA oxidative damage induced by copper (II)-ascorbic acid [25]; anxiolytic -like effect of a salmon phospholipopeptidic complex composed of polyunsaturated fatty acids and bioactive peptides associated with strong free radical scavenging properties [26]; antinociceptive activity in extracts of the skin of the Brazilian planehead filefish Stephanolepis hispidus with partial activation of opioid receptors in the nervous system [27]; strong in vitro acetylcholinesterase inhibition, an enzyme targeted by drugs used to treat Alzheimer’s disease, myasthenia gravis and glaucoma, by an extract from the polar marine sponge Latrunculia sp. [28]; central nervous system activity of a phlorotannin-rich extract from the edible brown seaweed Ecklonia cava targeting gamma-aminobutyric acid type A benzodiazepine receptors [29]; and novel protease inhibitors from Norwegian spring spawning herring determined by screening of marine extracts with assays combining fluorescence resonance energy transfer activity and surface plasmon resonance spectroscopy-based binding [30].…”
Section: Introductionmentioning
confidence: 99%
“…The radical scavenging effect on DPPH of compounds 1 – 5 were determined according to previously reported methods [27,28], and 2,6-ditertbutyl-4-methylphenol was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%